Description Of Suffering Duration, Self-Care Behavior, And Grade In Hypertension Patients - Rio Gita Rahma; Nina Indriawati ((JKG) Jurnal Keperawatan Global, 2022)
Background: Hypertension is often called "the silent killer" because it is often without complaints. The patient does not know that he has hypertension but then finds himself having complications from hypertension such as heart disease, stroke, kidney disease, blood vessel disease, to nervous disorders. Therefore, it is necessary to measure the level of self care Behaviour using a behavior scale to anticipate self-care Behaviour that is usually carried out by hypertensive patients.   Methods: Observational research using suffering duration, self-care behavior, and grade in hypertension for the Independent Variable. The number of samples used was 88 respondents, and the sampling technique used was Random Sampling. The instrument used in this study was a questionnaire using the Hypertension Self Care Profile (HBP-SCP) Behavior Scale questionnaire, which consisted of 20 statements. By using descriptive analysis.   Results: The results of univariate analysis of most of the patients aged 46-55 years (60.2%), female (57%), with a history of the last education level of elementary school (30%), family income per month of 2,000,000.00-4,000,000,00 (54.5%), duration of hypertension with short duration of 1-5 years (69%), self-care behavior in the moderate category (68%), and the majority were in grade 1 (48%).   Conclusion: Most respondents with a duration of illness of 1-5 years apply self-care behavior in the moderate category and are in the Garde 1 hypertension degree category at the Sultan Agung Hospital Semarang Polyclinic in 2022.